Upregulation of Atypical Cadherin FAT1 Promotes an Immunosuppressive Tumor Microenvironment via TGF-β - Irshad, Khushboo; Srivastava, Chitrangda; Malik, Nargis; Arora, Manvi; Gupta, Yakhlesh; Goswami, Sanjeev; Sarkar, Chitra; Suri, Vaishali; Mahajan, Swati; Gupta, Deepak Kumar; Suri, Ashish; Chattopadhyay, Parthaprasad; et al. (Frontiers in Immunology, 2022)
Atypical cadherin FAT1 promotes glioblastoma (GBM) by promoting pro-tumorigenic inflammatory cytokine expression in tumor cells. However, tumors also have an immunosuppressive microenvironment, maintained by mediators like TGF-β cytokines. Here, we have studied the role of FAT1 in tumor immune suppression. Our preliminary TIMER2.0 analysis of TCGA database revealed inverse correlation of FAT1 expression with infiltration of tumor-inhibiting immune cells (like monocytes, T-cells, etc.) and positive correlation with tumor-promoting immune cells (like myeloid-derived suppressor cells/MDSCs) in various cancers. We have analysed the role of FAT1 in modulating expression of TGF-β1/2 in resected human gliomas, primary glioma cultures and other cancer cell lines (U87MG, HepG2, Panc-1 and HeLa). Positive correlations of gene expression of FAT1 and TGF-β1/2 were observed in various cancers in TCGA, GLASS and CGGA databases. Positive expression correlations of FAT1 were also found with TGF-β1/2 and Serpine1 (downstream target) in fresh-frozen GBM samples using q-PCR. siRNA-mediated FAT1 knockdown in cancer cell lines and in primary cultures led to decreased TGF-β1/2 expression/secretion as assessed by q-PCR, Western blotting and ELISA. There was increased chemotaxis (transmigration) of THP-1 monocytes towards siFAT1-transfected tumor cell supernatant, as a consequence of decreased TGF-β1/2 secretion. Reduced TGF-β1 expression was also observed in THP-1 cultured in conditioned media from FAT1-depleted glioma cells, thus contributing to immune suppression. In U87MG cells, decreased TGF-β1 upon FAT1 knockdown was mediated by miR-663a, a known modulator. FAT1 expression was also observed to correlate positively with the expression of surrogate markers of MDSCs (PD-L1, PD-L2 and IL-10) in glioma tumors, suggesting a potential role of FAT1 in MDSC-mediated immunosuppression. Hence, our findings elaborate contributions of FAT1 to immune-evasion, where FAT1 enables an immunosuppressive microenvironment in GBM and other cancers via TGF-β1/2.